2022
DOI: 10.2147/idr.s375869
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genetic Variants Associated with Rifampicin Resistance Level in Mycobacterium tuberculosis Clinical Isolates Collected in Guangzhou Chest Hospital, China

Abstract: Rifampicin (RIF)-resistance, a surrogate marker for multidrug-resistant tuberculosis (TB), is mediated by mutations in the rpoB gene. We aimed to investigate the prevalence of mutations pattern in the entire rpoB gene of Mycobacterium tuberculosis clinical isolates and their association with resistance level to RIF. Methods: Among 465 clinical isolates collected from the Guangzhou Chest Hospital, drug-susceptibility of 175 confirmed Mtb strains was performed via the proportion method and Bactec MGIT 960 system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…However, it could be influenced by different regions and genetic strains. In a study that occurred in Guangzhou Chest Hospital of China, 85.71% were RIF-resistant, of which 38% were MDR-TB [35]. A study from Myanmar showed 62% isolates had RIF resistance [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be influenced by different regions and genetic strains. In a study that occurred in Guangzhou Chest Hospital of China, 85.71% were RIF-resistant, of which 38% were MDR-TB [35]. A study from Myanmar showed 62% isolates had RIF resistance [36].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of MDR-TB is a serious public health problem. 34 The SLDs have to be used for treatment of MDR/XDR-TB patients but are consistently difficult with less effectiveness, less availability in low-income countries, more toxicity, and higher costs. Susceptibility testing using MIC instead of the CCs shows that some FLDs act inhibitory in slightly higher concentrations in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The type and frequency of rpoB mutations related to RIF resistance may vary depending on the setting and level of resistance. 34 When compared to M. tuberculosis populations with isolates exhibiting high MICs, isolates with low-level resistance may have lower fitness in the presence of RIF. The cost of resistance has been identified as a crucial factor in the spread of DR-TB strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected individuals can unknowingly spread the disease to others, as the progression from latent TB infection to active TB disease can occur gradually over time. Also, in most cases, the infected patients remain undiagnosed, posing a significant risk of widespread transmission of infection ( 3 ). The presence of undiagnosed rifampicin-resistant (RIF R ) cases has exacerbated the global health situation and contributed to the escalating burden of TB ( 4 ).…”
Section: Introductionmentioning
confidence: 99%